Osmotic hemolysis is a donor‐specific feature of red blood cells under various storage conditions and genetic backgrounds. Issue 9 (19th June 2021) - Tzounakas, Vassilis L.; Anastasiadi, Alkmini T.; Valsami, Serena I.; Stamoulis, Konstantinos E.; Papageorgiou, Effie G.; Politou, Marianna; Papassideri, Issidora S.; Kriebardis, Anastasios G.; Antonelou, Marianna H.
Abstract: Background: Transfusion research has recently focused on the discovery of red blood cell (RBC) storage capacity biomarkers and the elucidation of donor variation effects. This shift of focus can further strengthen personalization of transfusion therapy, by revealing probable links between donor biology, RBC storage lesion profile, and posttransfusion performance. Study design and methods: We performed a paired correlation analysis of osmotic fragility in freshly drawn RBCs and during cold storage in different preservative solutions at weekly intervals until unit's expiration date ( n  = 231), or following 24 h reconstitution in allogeneic plasma ( n  = 32) from healthy controls or transfusion‐dependent beta‐thalassemia patients. Results: We observed exceptional correlation profiles ( r  > 0.700, p  < 10 −5 in most cases) of RBC osmotic fragility in the ensemble of samples, as well as in subgroups characterized by distinct genetic backgrounds (sex, beta‐thalassemia traits, glucose‐6‐phosphate dehydrogenase deficiency) and storage strategies (additive solutions, whole blood, RBC concentrates). The mean corpuscular fragility (MCF) of fresh and stored RBCs at each storage time significantly correlated with the MCF of stored RBCs measured at all subsequent time points of the storage period (e.g., MCF values of storage day 21 correlated with those of storage days 28, 35 and 42). A similar correlation profile was also observed between the osmotic hemolysis of fresh/stored RBCs before and following in vitro reconstitution in plasma from healthy controls or beta‐thalassemia patients. Conclusion: Our findings highlighted the potential of osmotic fragility to serve as a donor‐signature on RBCs at every step of any individual transfusion chain (donor, blood product, and probably, recipient).